Self-healing enhancing tensile creep of 2D-satin weave SiC/(SiC-SiBCN)x composites in wet oxygen environment. Issue 10 (August 2020) - Luan, Xingang; Xu, Xinming; Wang, Lei; Zou, Yun; Yu, Zhaoju; Cheng, Laifei; Riedel, Ralf
Abstract: In order to further expand the application of SiC/SiC composites in the hot-end components for advanced aerospace engines, a self-healing SiC/(SiC-SiBCN)x composite prepared by CVI + PIOP has been tested for their creep behavior at 1200 °C with the partial pressure of 12 kPa H2 O: 8 kPa O2 : 80 kPa Ar. For the samples tested under low stresses, the load is borne by a load-bearing region, so that the secondary stage of creep curves can be subdivided into several small steps. Besides, it is found that the number of defects in SiC/(SiC-SiBCN)x composites is predominantly related to the stress level while the size of the defects is related to the creep time. Our findings provide important analytical data related to the creep behavior of the SiC/(SiC-SiBCN)x composite material and contribute to the further development of CMCs with outstanding mechanical properties and corrosion resistance even under harsh environments.